2020
DOI: 10.1101/2020.04.20.047845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reprogramming acetogenic bacteria with CRISPR-targeted base editingviadeamination

Abstract: Acetogenic bacteria are rising in popularity as chassis microbes in biotechnology due to their capability of converting inorganic one-carbon (C1) gases to organic chemicals. To fully uncover the potential of acetogenic bacteria, synthetic-biology tools are imperative to either engineer designed functions or to interrogate the physiology. Here, we report a genome-editing tool at a one-nucleotide resolution, namely base editing, for acetogenic bacteria based on CRISPR-targeted deamination. This tool combines nuc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Cas9 variants, which mainly include Cas9 nickase (D10A, usually denoted nCas9) and catalytically inactive Cas9 (D10A/H840A, usually denoted dCas9), fuse with deaminases to induce C:G to T:A or A:T to G:C conversion ( 19 ). Numerous tools derived from BEs have been successfully applied in gene insertions, gene deletions, and point mutations in various bacterial ( 20–24 ), mammalian ( 25–27 ) and plant cells ( 28–30 ). Due to the diverse genome environments in diverse cells and host-dependent factors of some tools, one tool is usually applied for one kind of cell.…”
Section: Introductionmentioning
confidence: 99%
“…Cas9 variants, which mainly include Cas9 nickase (D10A, usually denoted nCas9) and catalytically inactive Cas9 (D10A/H840A, usually denoted dCas9), fuse with deaminases to induce C:G to T:A or A:T to G:C conversion ( 19 ). Numerous tools derived from BEs have been successfully applied in gene insertions, gene deletions, and point mutations in various bacterial ( 20–24 ), mammalian ( 25–27 ) and plant cells ( 28–30 ). Due to the diverse genome environments in diverse cells and host-dependent factors of some tools, one tool is usually applied for one kind of cell.…”
Section: Introductionmentioning
confidence: 99%
“…The mixed populations of edited strains seem to be a common issue for base editing, which have been observed in different microbes, such as C. ljungdahlii, Clostridium beijerinckii , and Agrobacterium spp. (29, 31, 36). Moreover, we achieved, to our best knowledge, the first multiplex genome editing in the species of Synechococcus , and two distant loci with completely different protospacers were edited simultaneously (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Base editing has been successfully adapted in bacteria, such as Streptomyces griseofuscus, Agrobacterium rhizogenes, Pseudomonas putida and Clostridium ljungdahlii (28)(29)(30)(31). To be noticed, Xia et al (2020) reported the potential of base editing in metabolic engineering of Clostridium ljungdahlii via a genome-scale interrogation, and demonstrated that base editing could overcome the challenges of applying CRISPR-Casbased genome-editing in bacteria, including the toxicity. Therefore, base editing may also shed light on the development of genome-editing tools for cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…), and inverse PCRs were following previously established protocols in the lab. 28 Plasmid extraction and purification were conducted using commercial kits from Tiangen Biotech. PCRs were performed with PrimeSTAR Max DNA Polymerase from Takara Bio.…”
Section: Methodsmentioning
confidence: 99%